Etika Bisnis dalam Kunjungan dan Pelayanan Tamu Jepang - Anaqi, Amar Fawwas; Priventa, Hendrike (KIRYOKU, 2024)
This research aimed to identify business ethics that could be applied in visits and guest services for Japanese clients, considering the increasingly globalized business landscape. Given the necessity of collaborating with foreign partners, including Japanese individuals, this study employed a qualitative approach using observational methods based on the author's five years of experience in the Japanese business world. The findings revealed the importance of implementing appropriate ethics in all aspects of interaction, from airport pick-ups and in-car etiquette to hotel and dining manners, as well as accompanying guests on tours and receiving visitors at the company. Such practices fostered stronger relationships and enhanced trust with Japanese business partners. Business professionals needed to be adaptable and capable of building positive relationships with various stakeholders. Consequently, learning and applying business ethics was essential for any businessperson.